2012
DOI: 10.1590/s0100-40422012000300002
|View full text |Cite
|
Sign up to set email alerts
|

Poly(o-methoxyaniline) modified electrode for detection of lithium ions

Abstract: Recebido em 16/2/11; aceito em 12/9/11; publicado na web em 8/11/11 This paper reports the use of an electrode modified with poly(o-methoxyaniline) for detecting lithium ions. These ions are present in drugs used for treating bipolar disorder and that requires periodical monitoring of the concentration of lithium in blood serum. Poly(omethoxyaniline) was obtained electrochemically by cyclic voltammetry on the surface of a gold electrode. The results showed that the electrode modified with a conducting polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Standard techniques for blood lithium measurement such as FEP or atomic absorption spectroscopy (AAS) are not suitable for such applications because they are laboratory-based, cumbersome, expensive, and complex to operate. 11 Other techniques that have been adapted to suit clinical and home diagnostics include electrophoresis, 12,13 ion-selective electrodes, 11,14,15 and impedance spectroscopy. 16 Ion-selective electrodes can be used for point-of-care testing for determining a range of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Standard techniques for blood lithium measurement such as FEP or atomic absorption spectroscopy (AAS) are not suitable for such applications because they are laboratory-based, cumbersome, expensive, and complex to operate. 11 Other techniques that have been adapted to suit clinical and home diagnostics include electrophoresis, 12,13 ion-selective electrodes, 11,14,15 and impedance spectroscopy. 16 Ion-selective electrodes can be used for point-of-care testing for determining a range of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to develop conductive polymer sensors for monitoring lithium levels [ 49 , 70 ]. Conductive polymers (CPs) and nanostructures are amongst commercial solid-contact ion-selective electrodes (SC-ISEs).…”
Section: Advances In Therapeutic Monitoring Of Lithium Levelsmentioning
confidence: 99%
“…Aniline and its derivatives have been extensively studied as conducting polymers due to their chemical stability, ease of polymerization and doping, as well as low cost [ 70 ]. Lindino et al reported the use of a gold electrode modified with poly(o-methoxyaniline), which is a derivative of aniline polymers, as the conducting polymer to respond to lithium ions in the concentration range of 1 × 10 −5 to 1 × 10 −4 mol L −1 [ 70 ]. The electrode modified with the conducting polymer showed a potentiometric response to Li+ concentration [ 70 ].…”
Section: Advances In Therapeutic Monitoring Of Lithium Levelsmentioning
confidence: 99%
“…Secondary dopants can also change the features of the polymer as a primary dopant Possible interaction between the polymer and secondary dopant can occur by covalent bonding, van der Waals forces or hydrogen bonding that leads to variation in conformation and charge transfer. The target analytes detected by the polymer modified electrodes are considered as secondary dopants and a charge transfer complex arise between polymer and target species .…”
Section: A Brief Overview and The Characteristics Of The Modificationmentioning
confidence: 99%